Competitiveness as the Basis of EU Regional Policy: Smart Specialization and Sustainability - Palinchak, Mykola; Tsalan, Myroslava; Brenzovych, Kateryna; Kucher, Anatolii; Kajánek, Tomáš; Grešš, Martin (European Journal of Sustainable Development, 2021)
Nowadays in the globalization era countries are forced to pay considerable attention to the integration aspects of development, regionalization processes ensuring their own competitiveness in order to enhance the competitive position in the market, which increases the scientific interest in the study of these issues. The purpose of the article is to consider competitiveness as the basis of EU regional policy and to determine the possibilities of applying such experience in Ukraine. A number of scientific research methods have been used: the method of deduction and induction, analysis, synthesis and comparison, a graphic method. Globalization contributes to the creation of new conditions of the world economic development, which forces economic actors to reconsider their role in the economy. Competitiveness provides them with a reliable competitive positions today and in the future. The high competitiveness of the region testifies to the effective organization and optimization of economic processes. EU regional policy takes into account that the competitiveness of the region is formed in the conditions of competitive relations at the national and international levels. The EU regional policy experience can be implemented in the Ukrainian regional policy. The competitiveness of the region allows to respond in time to market changes. EU regional policy takes this into account, so the category of regional competitiveness is paid much attention on as confirmed by the RCI calculation. The possibilities of increasing the competitiveness and sustainability of regions through the development of smart specialization and implementation of smart projects are outlined. The advantages of implementing European experience in the development of competitiveness of regions on the basis of smart specialization in Ukraine are proved.